Periodic Solutions of Nonlinear Wave Equations with Dissipative Boundary Conditions (Journal of Partial Differential Equations, 1990)
Applying Nash-Moser's implicit function theorem, the author proves the existence of periodic solution to nonlinear wave equation u_{tt} - u_{xx} + &#949g(t, x, u, u_t, u_x, u_{tt}, u_{tx}, u_{xx}) = 0 with a dissipative boundary condition, provided &#949 is sufficiently small.
Keywords: Nonlinear wave equation; time periodic solution; dissipative boundary condition